3207 Relation between Dopamine Transporter (DAT1) polymorphism and subjective effects of alcohol among non-dependent drinkers. (27th March 2019) - Soundararajan, Soundarya; Stangl, Bethany L.; Vaughan, Courtney L.; Sun, Hui; Lohoff, Falk; Schwandt, Melanie L.; Ramchandani, Vijay
Abstract : OBJECTIVES/SPECIFIC AIMS: Dopamine transporter (DAT1) gene variation is associated with reward-related phenotypes including alcohol response. There is also evidence for a potential moderating role for mu-opioid receptor (OPRM1) gene variation on the relationship between DAT1 variation and alcohol response measures. We aimed at studying the interaction between the DAT1 VNTR and OPRM1 A118G polymorphisms on alcohol consumption and subjective responses among non-dependent drinkers. METHODS/STUDY POPULATION: We employed a progressive ratio (PR) paradigm of intravenous alcohol self-administration (IV-ASA) using the Computer-Assisted Infusion System (CAIS) to assess the motivation for alcohol seeking and consumption in a sample of nondependent drinkers. We used the Drug Effects Questionnaire (DEQ) and Biphasic Alcohol Effects Questionnaire (BAES) to assess subjective response. IV-ASA measures included average breath alcohol concentration (BrAC) and total ethanol infused. Peripheral blood samples were collected for genotyping. Ethics approval was obtained from the NIH Addictions Institutional Review Board. RESULTS/ANTICIPATED RESULTS: Fifty participants completed the PR IV-ASA session after informed consent. There were significant interactions between the DAT1 and OPRM1 genotypes in subjective effects of alcohol. Simple main effects analysis showed that DAT1 10a allele carriers that were also OPRM1 G allele carriers had significantly higher scores for several measures: "feel the drug effects" (F (1, 46)=6.573, P = 0.014), "feel intoxicated"(F(1, 46)=8.613, P = 0.005) and "feeling high" (F(1, 46)=10.889, P = 0.002) in DEQ and higher sedation (F(1, 46)=4.575, P = 0.038) in BAES. The genotypes statistically significantly predicted average breath alcohol (F (1, 61) =3.295, p=0.044) and total ethanol infused(F(1, 61)=3.632, p=0.032. DAT1 VNTR and OPRM1 A118G polymorphisms taken together accounted for 6.9 and 7.8% of variations in average breath alcohol and total ethanol infused respectively. DISCUSSION/SIGNIFICANCE OF IMPACT: Polymorphic variations in DAT1 and OPRM1 interact with each other in determining subjective effects of alcohol in intravenous alcohol infusion assessing motivation for alcohol seeking and consumption in nondependent drinkers. These epistatic interactions in subjective effects of alcohol are salient in the context of predicting and understanding neurobiological effects of alcohol and thereby the therapeutic responses in treating alcohol use disorders.